2006
DOI: 10.2166/wp.2006.044
|View full text |Cite
|
Sign up to set email alerts
|

Privatisation of urban water service provision: the Kenyan experiment

Abstract: One of the services that have been poorly provided in the urban areas in Kenya is water and sanitation. There are many reasons, which can be attributed to poor provision of water and sanitation as undertaken by the local authorities in Kenya. The path to remedy the poor provision of water and sanitation has been charted in privatisation in the form of commercialisation. Commercialisation in Kenya was first implemented on an experimental basis in three urban areas: Nyeri, Eldoret and Nakuru. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…The information was used to examine the totality of relationship between revenue generation aspects and the utility's financial sustainability. Based on the positivist and constructivist thoughts, the investigator applied a mixed methods approach; where quantitative methods elicited information for descriptive and inferential purposes, while qualitative methods obtained detailed case analysis information for validating quantitative results (Sale, Lohfeld & Brazil, 2002;Hughes & Sharrock, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…The information was used to examine the totality of relationship between revenue generation aspects and the utility's financial sustainability. Based on the positivist and constructivist thoughts, the investigator applied a mixed methods approach; where quantitative methods elicited information for descriptive and inferential purposes, while qualitative methods obtained detailed case analysis information for validating quantitative results (Sale, Lohfeld & Brazil, 2002;Hughes & Sharrock, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…(K'akumu & Appida, 2006) reported that local authorities interfered in the running of the water utilities that they had incorporated. WASREB cite political interference as a threat to the management and activities of WSPs (WASREB, 2015).…”
Section: Governancementioning
confidence: 99%
“…supplying water). Symptoms of poor governance identified included: unaccounted for water, lack of Water Governance in Barbados 157 metering, ineffective collection of water revenue, uneconomic tariffs, exclusion of the poor from the service, excess staff of water service provider, conflict of roles in water management and little connection to municipal sewerage network (Panayotou, 1997;K'Akumu and Appida, 2006). Problems associated with poor or inadequate provision of water services and water resources management have been the subject of investigation by a wide range of authors with a variety of explanations given.…”
Section: What Is Water Governance?mentioning
confidence: 99%